Polymer positive temperature coefficient composites with room-temperature Curie point and superior flexibility for self-regulating heating devices. (16th January 2023) - Zhou, Can; Zhang, Yangyang; Cen, Fangjie; Yu, Xie; Zhou, Wenjing; Jiang, Shenglin; Yu, Yan
Abstract: Polymer PTC (positive temperature coefficient) materials with low switching temperature point are important for many electronic devices since the electronic devices usually work under room temperature range (0–40 °C). The desired polymer PTC materials for the application in thermal control of flexible electronics should also include room-temperature switching temperature, low room-temperature resistivity, good mechanical flexibility and adaptive thermal control performances. This work designed two new types of PTC materials with room-temperature switching temperature and excellent mechanical properties. They are prepared by mixing the semi-crystalline polymer EVA with low melting temperature (Tm) with the amorphous polymer (PS or PVAc) with low glass transition temperature (Tg), while the low-cost graphite is selected as conductive filler. The PTC materials were obtained with low switching temperature point (<30 °C) and low room temperature resistivity (102 Ω m), high PTC repeatability and flexibility, short heating response time and good adaptive thermal control performances. Graphical abstract: Image 1 Highlights: Conductive composites with low Curie point were prepared by simple process. Binary polymers improve the repeatability of composites. Polymer compatibility affects the microstructure and conductive network. Elastic EVA improves the mechanical properties of composites. The self-regulating heating temperature can be controlled between 30 and 50 °C.